Lipid profile variations in high olecic acid peanuts by following different cooking processes. (May 2022) - Xiao, Yuan; Liu, Hao; Lu, Qing; Li, Haifen; Liu, Qinjian; Li, Shaoxiong; Liu, Haiyan; Varshney, Rajeev K.; Liang, Xuanqiang; Hong, Yanbin; Chen, Xiaoping
Graphical abstract: Highlights: 706 lipids are identified in high oleic acid (HOA) peanuts. Lipid substances are maximally retained in boiled HOA groundnut. Frying generates 242 different lipids, not an appropriate treatment for HOA peanut. GC–MS quantifies fatty acids to cross-validate lipidomic results. Abstract: High oleic acid (OA) peanut seed (PS), contains a higher ratio of oleic acid (C18:1) compared to general PS, which is favored by consumers due to its health benefits. However, comprehensive lipid metabolite profiles of high-OA PS, once they have been processed via domestic cooking methods, have never been produced. To establish a scientific guide for the selection of the most appropriate processing method for high-OA PS, lipidomics was performed to identify 706 lipid metabolites in high-OA PS following boiling, baking and frying, between the three groups, 75, 175 and 242 lipid metabolites were differentially expressed respectively. Additionally, 46 glycerolipids with C18:1 molecular were observed in the lipid profiles of the treatment groups compared to the raw sample. Further evaluation of seven lipid peroxides and six antioxidant status of each testing group suggested that boiled PS retained the highest levels of lipids and antioxidant activity. Following these findings, boiling appears to be an appropriate processing method when attempting to conserve the beneficial substances found in the PS. Finally, the levels of major free fatty acids present in high-OA PS, were jointly quantified by conventional methods (GC-MS) and lipidomic analysis. FA/C16:0 levels were similar, FA/C18:0, FA/C18:1 displayed opposite results, FA/C18:2 levels increased following frying and FA/C18:3 levels were down regulated once the PS was boiled. This indicates that GC-MS is a potential method of validation for the results of lipidomic analysis. Conclusively, this in depth understanding of lipid content in relation to domestic cooking methods has provided a foundation for the processing of high-OA peanut products.